Methods in insect sensory neuroscience - Christensen, Thomas A. (CRC Press, 2005)
Written by recognized experts in sensory biology, Methods in Insect Sensory Neuroscience synthesizes the latest information and reviews the most current methods for studying the specialized sensory systems of insects. Bridging the gap between experimentalists and theorists, the book covers a wide range of techniques, including anatomical pathway tracing, electrophysiological recording, genetic and pharmacological manipulations, computational modeling, and behavioral observations. Each chapter discusses the most challenging questions facing sensory neuroscience today and provides a unique synopsis of the developments that are driving the field forward.